Isotonitazene: Fatal intoxication in three cases involving this unreported novel psychoactive substance in Switzerland. (March 2021) - Mueller, F.; Bogdal, C.; Pfeiffer, B.; Andrello, L.; Ceschi, A.; Thomas, A.; Grata, E.
Highlights: Isotonitazene quantification in human post-mortem tissues, blood and hair. Isotonitazene accumulation in brain and hearth and very low concentration in liver. Isotonitazene powder determination using GC-MS, NMR. Very low isotonitazene concentration in blood can be fatal. Abstract: The paper describes the first three deaths reported in Europe involved in isotonitazene consumption, a potent benzimidazole derivate opioid consumed in the recreational drug scene. Isotonitazene powder and purity determination was performed on the sample collected in the first death scene by NMR, HRMS, GC-FTIR, ATR-FTIR and GC–MS. Isotonitazene purity was determined by GC–MS analysis and proton NMR, and was defined to be above 95 % and 98 %, respectively. Quantification of isotonitazene in biological samples was performed using a targeted analysis based on SPE extraction and ultra-high performance liquid chromatography tandem mass spectrometry. The isotonitazene median concentration in femoral whole blood was 1.20 ng/mL. Isotonitazene concentration in hair was similar or even lower compared to that seen in fentanyl abusers. Isotonitazene distribution in tissues converges in the brain, lungs and heart, respectively. Surprisingly, isotonitazene concentration in liver is the lowest measured for all tissues and fluids analyzed. Based on circumstantial evidence, autopsy findings and the results of the toxicological analysis, the medical examiner concluded that the cause of all three deaths was an acute intoxication with isotonitazene. Since isotonitazene toxic concentration levels are very low, the consumption of this new psychoactive drug is a real hazard for human health.